Distinctive pattern of AHNAK methylation level in peripheral blood mononuclear cells and the association with HBV‐related liver diseases. (27th September 2018) - Sun, Libo; Li, Kang; Liu, Guihai; Xu, Yuan; Zhang, Aiying; Lin, Dongdong; Zhang, Haitao; Zhao, Xiaofei; Jin, Boxun; Li, Ning; Zhang, Yonghong
Abstract: The purpose of this study was to investigate the correlation between AHNAK methylation level in peripheral blood mononuclear cells (PBMC) and the progression of hepatitis B virus (HBV)‐related liver disease. Bioinformatics methods were applied to evaluate the AHNAK methylation level in PBMC and T cells at different stages of HBV related liver disease, to investigate the correlation between AHNAK methylation and clinical features, as well as to compare the methylation site of AHNAK in cancer tissues and adjacent tissues. Subsequently, the differentially expressed gene analysis technique was used to analyze the liver disease‐related genes and immune‐related pathways in hepatitis B patients with different pathological changes. Finally, promoter methylation and mRNA expression of AHNAK gene in liver cancer and adjacent tissues were determined by quantitative polymerase chain reaction (Q‐PCR), and the diagnostic value of AHNAK methylation level in hepatopathy was evaluated by receiver operating characteristic (ROC) curve. The promoter methylation level of AHNAK gene in PBMCs decreased with the progression of HBV‐related liver disease, and showed significant difference among the patients with various HBV‐related liver diseases ( P = 0.0001). The AHNAK methylation level in PBMCs and T cells was negatively associated with age, white blood cell count, CREA, drinking, and positively associated with APTT and HbsAg. Higher mRNA expression of AHNAK was found in liver cancer tissues than that of adjacent tissues ( P < 0.001), and the methylation level in PBMC decreased with the progression of hepatitis B‐related liver disease. The area under the ROC curve (ROC) was 0.883 ( P < 0.001) in diagnosis of chronic hepatitis B (CHB), 0.885 ( P < 0.001) in diagnosis of compensatory liver cirrhosis, 0.955 ( P < 0.001) in diagnosis of decompensated liver cirrhosis, 0.981 ( P < 0.001) in diagnosis of hepatocellular carcinoma. Our results revealed that AHNAK methylation level in peripheral blood decreases with the progression of hepatitis B‐related liver disease. This provided a potential differential diagnostic method for HBV‐related hepatopathies, and thus an early detective tool for liver cancer. Abstract : AHNAK might be a potential diagnostic marker for early detection of liver cancer. AHNAK was higher expressed in liver cancer tissues. The methylation level of AHNAK in PBMC decreased with the progression of hepatitis B‐related liver disease.